Differences in seed dormancy associated with the domestication of Cucurbita maxima : Elucidation of some mechanisms behind this response - Martínez, Analía Beatriz Luján (2018)
This work presents the results of physiological studies developed to understand modifications linked to the reduction of seed dormancy provoked by domestication processes. The experiments performed compared wild and domesticated Cucurbita subspecies and their hybrids developed by reciprocal crossings. Seeds of two accessions of the wild subspecies presented dormancy, but it was largely reduced in seeds from the domesticated genotype, and partially reverted in hybrids, especially in those obtained when the domesticated genotype was used as the mother plant. In addition, naked embryos of all subspecies did not display dormancy when incubation was performed at 28°C, but embryo germination was progressively reduced only in the wild genotype under decreasing incubation temperatures (22 and 16°C). In the embryos, abscisic acid (ABA) concentrations were similar in both domesticated and wild subspecies, whereas in the seed coat, it was threefold higher in the wild subspecies. The naked embryos from the wild subspecies were far more responsive to ABA than those from the domesticated subspecies. These results indicate that dormancy in the wild subspecies is imposed by the seed coat tissues and that this effect is mediated by their high ABA content and the sensitivity of the embryos to ABA. These physiological aspects were apparently removed by domestication along with the temperature-dependent response for germination.